Automorphism groups of Cayley evolution algebras - Costoya Ramos, María Cristina; Muñoz, Vicente; Tocino-Sánchez, Alicia; Viruel-Arbaizar, Antonio Ángel (Springer Nature, 2023)
In this paper we introduce a new species of evolution algebras that we call Cayley evolution algebras. We show that if a field k contains sufficiently many elements (for example if k is infinite) then every finite group G is isomorphic to Aut(X) where X is a finite-dimensional absolutely simple Cayley evolution k-algebra.
Keywords: Álgebra; Evolution algebra; Finite group; Automorphism group; Graph